The Influence of Customer Trust, Technological Innovation And Ease of Transaction on The Satisfaction of Users of The Brimo Application at Bank Bri Magetan Branch - Ashari, Muchammad Fachrul (CV. Publikasi Indonesia, 2025)
A bank is an institution that collects funds from the community in the form of deposits and distributes them to the community through credit or other forms, with the aim of improving people's living standards. As a company engaged in services, the bank offers services to the community. This study aims to explore the influence of customer trust, technological innovation, and ease of transaction on the satisfaction of BRImo application users at Bank BRI Magetan, by using Net Promoter Score (NPS) as an evaluation tool. Although Bank Magetan has an NPS score of 62.5 which indicates a good level of satisfaction, there are indications that there are gaps in customer experience that need to be improved. The digital transformation carried out by Bank BRI through the BRImo application has great potential to increase customer loyalty. This study uses an explanatory research method with a quantitative design, involving 96 customers of Bank BRI Magetan as a sample. The results of the analysis show that customer trust, technological innovation, and ease of transaction have a significant positive effect on customer satisfaction. The significance value for customer trust is 0.001, for technological innovation 0.006, and for ease of transaction 0.008. All of these significance values are less than 0.05, indicating that these three factors have a significant contribution to customer satisfaction of the BRImo application at Bank BRI Magetan.